THE ROLE OF CAREER DEVELOPMENT AND WORK-LIFE BALANCE ON JOB SATISFACTION THROUGH WORK ENGAGEMENT - Istikarani, Miranda; Rosnani, Titik; Marumpe, Dody Pratama; Daud, Ilzar; Karsim, Karsim (International Journal of Economics, Business and Accounting Research (IJEBAR), 2024)
This study examines the role of career development and work-life balance on job satisfaction among healthcare workers in Kubu Raya, West Kalimantan, with a focus on work engagement as a mediating variable. Utilizing a quantitative approach, data were collected from 210 health workers through a structured questionnaire and analyzed using Structural Equation Modeling (SEM) and tools AMOS to processed the data. The results of this study indicate that career development and work-life balance have a positive and significant impact on job satisfaction. Additionally, this research successfully tested the role of work engagement in mediating the indirect effect of career development and work-life balance on job satisfaction. Although the work engagement variable can mediate the relationship between career development and job satisfaction, it has not been able to mediate the relationship between work-life balance and job satisfaction. Furthermore, work engagement in this study also has a positive and significant effect on job satisfaction. These results will underscore the importance of fostering career growth opportunities and promoting a balanced work-life environment to enhance employee satisfaction and performance. The insights gained from this research offer valuable guidance for healthcare organizations and policymakers aiming to improve workforce well-being and organizational productivity.